2021
DOI: 10.1017/s1368980021002287
|View full text |Cite
|
Sign up to set email alerts
|

Developing sugar-sweetened beverage warning labels for young adults

Abstract: Objective: There is a lack of qualitative research developing sugar-sweetened beverage (SSB) warning labels with their intended end-users. We sought to identify promising SSB warning elements for improving label effectiveness and for future testing in policy and institutional settings. Design: Mixed-methods design using 10 focus groups, a design task, and survey. The design task was used to generate ideas for an icon that would dissuade SSB consumption. The survey and focus group guide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Label shape and use of the signal word, “warning”, facilitated perceptions of seriousness and credibility across all label types similar to previous studies [ 34 , 39 , 40 ]. Consistent with the previously mentioned study of young adults [ 40 ], comparisons were drawn with government tobacco warnings, stop sign shapes and danger warnings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Label shape and use of the signal word, “warning”, facilitated perceptions of seriousness and credibility across all label types similar to previous studies [ 34 , 39 , 40 ]. Consistent with the previously mentioned study of young adults [ 40 ], comparisons were drawn with government tobacco warnings, stop sign shapes and danger warnings.…”
Section: Discussionsupporting
confidence: 83%
“…These studies have explored reactions to a broader range of potential warning labels on SSBs. The mixed-methods US study of college students’ (n = 86) perceptions of a range of potential SSB warnings (on-product and point of sale) found for text-only messages, attribution to the college health centre increased perceived effectiveness by increasing credibility [ 39 ]. Brevity and clarity of the messages were valued, as were warnings with a picture/icon.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior qualitative research, pregnant women and parents of infants identified graphic warning labels as the preferred option to motivate SSB reduction for themselves and their infants [24]. Similarly, a mixed-methods study found that young adults perceived warning labels with graphics or icons to be more effective and preferable to text-only labels [49].…”
Section: Discussionmentioning
confidence: 88%
“…Our findings also support the idea that effective HWL are often less acceptable ( 16 , 17 ) . Nevertheless, SSB warning labels with loss-frame messages, promoting messages similar to the HWL used in this study, have been proven more effective than gain-frame messages ( 33 ) . Therefore, instead of avoiding such graphic HWL, the task at hand, perhaps, is to discover ways of increasing HWL acceptance, for instance, by complementing it with effectiveness information ( 27 ) .…”
Section: Discussionmentioning
confidence: 92%